Model Home : A Proposition by Michael Lin : 2012. - Lin, Michael; Liao, Ella; Ou, Thomas; Frogier, Larys; Hsiangling, Lai; Munroe, Alexandra; Hanru, Hou; Hasegawa, Yuko; Yao, Pauline J.; Xiangning, Li (Shanghai : RAM Rockbund Art Museum, 2012)
Lin, Michael ; Atelier Bow-Wow ; Ran, Cheng ; Xiangning, Li ; Nanli, Lou
Model Home: A Proposition by Michael Lin, Rockbund Art Museum, Shanghai, 10 March 2012 - 3 June 2012
boek
Keywords: Lin, Michael